Update of the problems of psychosocial assistance to the population of Ukraine in the conditions of war - Khadzhyradieva, Svitlana; Todorova, Marianna (Public Administration and Regional Development, 2023)
The article presents the scientific justification of the problems of psychosocial assistance to the population of Ukraine in war conditions, in particular, the results of the analysis of the state of organizational and legal support of institutions whose activities are aimed at psychosocial assistance to the population are presented, and also the basic needs of people who have fallen into an extreme life situation in psychosocial support The low reliability of medical statistics regarding cases of morbidity and prevalence, in particular conditions related to psychosomatic disorders, was found. The annual growth of outpatient consumption of antidepressants was revealed, which became the main reasons for structural changes in the provision of mental health care to the population of Ukraine. In addition, it should be noted that the organizational and legal support of institutions whose activities are aimed at psychosocial assistance to the population needs further improvement. The first step has been taken - under the auspices of the President’s wife Olena Zelenska, the creation of the "National Program of Mental Health and Psychosocial Support of the Population" has been initiated in Ukraine. The program, with the support of WHO specialists, will cover the issue of training and education of psychologists and psychotherapists, family doctors, social workers, and educators in rapid methods of psychological support for the population affected by hostilities and martial law. The results of the assessment of the basic needs of persons caught in an extreme life situation in psychosocial support in the conditions of war are presented. The broader development of the system of providing psychosocial assistance to the population by multidisciplinary teams consisting of a psychiatrist, psychologist (practical, clinical, psychotherapist), social worker, rehabilitator, etc. is important. The coordination of integrated work in a multidisciplinary team is carried out by the specialist whose help is of primary importance at the current moment, depending on the patient’s needs.